Nursing care managerial strategies in coronary care unit: evaluation of three public university hospitals in Rio de Janeiro - preview note - Marluci Andrade Conceição Stipp; Daniele Fernandes Aguiar (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The research refers to a Master's Dissertation Project developed in the Nursing Post Graduation Program in Anna Nery School of Nursing / UFRJ. Objectives: to identify managerial strategies used by nurse leaders in the Coronary Care Unit in public university hospitals; to describe the nursing care management carried out by nurse leaders in the Coronary Care Units at public university hospitals; and to analyze the managerial strategies developed by nurse leaders in the nursing care management in the Coronary Care Unit at public university hospitals. This is a multiple case study, with a qualitative approach. The subjects will be the nurses who work in three public university hospitals in Rio de Janeiro and who provide direct care to patients from Coronary Care Units: Clementino Fraga Filho University Hospital (HUCFF), Pedro Ernesto University Hospital (HUPE) and Antônio Pedro University Hospital (HUAP). Data collection will be made with the help of semi-structured interviews, and direct and informal observation of the subjects, complying with the precepts established from Resolution number 196/96. The conclusion of the stage of this methodology will be determined by the data saturation criterion. Data will be grouped, classified and evaluated through categories.